2000
DOI: 10.1017/s1461145700002017
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of clinical data to identify subtypes within a study population following treatment with a new pentapeptide antidepressant

Abstract: Cluster analysis was used to evaluate the data from a placebo-controlled, double-blind clinical trial with a new pentapeptide antidepressant (INN 00835) in major depression. The objective of this paper is to examine the effect of separating the study population into homogeneous subgroups (clusters) with relatively similar response to treatment within subgroups, and significantly different response between subgroups. The list of variables for cluster analysis was selected only from the efficacy parameters inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The first study clustered MDD subjects based on improvement after treatment (at 7-and 14-day follow-up) with netamiftide (a synthetic pentapeptide antidepressant) and subsequently measured platelet 5-hydroxytryptamine (5-HT) uptake levels [65]. This study found four subgroups with increasing levels of symptom improvement.…”
Section: Medication Responsementioning
confidence: 99%
“…The first study clustered MDD subjects based on improvement after treatment (at 7-and 14-day follow-up) with netamiftide (a synthetic pentapeptide antidepressant) and subsequently measured platelet 5-hydroxytryptamine (5-HT) uptake levels [65]. This study found four subgroups with increasing levels of symptom improvement.…”
Section: Medication Responsementioning
confidence: 99%
“…The lack of adverse events in these studies (data on file) allowed the administration of similar doses in the first two efficacy studies reported separately [2][3][4][5].…”
Section: Methodsmentioning
confidence: 99%
“…Nemifitide is the lead compound in a series of highly potent small-chain peptides synthesized at Innapharma [1]. In two previously conducted pilot phase 2 double-blind, placebo-controlled trials [2][3][4][5] nemifitide was administered subcutaneously for 5 or 10 days to patients diagnosed with major depression. The doses administered in these studies were similar: 18 mg/patient and 0.2 mg/kg, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…INN 00835 (netamiftide) is a novel pentapeptide from a new platform of small chain putative peptide antidepressant agents [124][125][126][127]. Its mechanism of action is unclear, but it may involve serotonergic and dopaminergic pathways, as well as peptide receptors.…”
Section: Inn 00835mentioning
confidence: 99%